2015
DOI: 10.1002/cphc.201500101
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Phase Affinity Scales for Typical Ionic Liquid Moieties Determined by using Cooks’ Kinetic Method

Abstract: Gas-phase affinity studies based on cations and anions commonly present in ionic liquid structures, give quantitative information about the magnitude of the interactions holding the two species together when ILs are formed. They also provide clues on how these interactions depend on the nature of the cationic and anionic moieties. In the present work, mass spectrometric experiments, performed using electrospray ionization quadrupole ion-trap and Fourier transform ion cyclotron resonance mass spectrometry, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Based on the relative center-of-mass collision energies at 50% dissociation, the relative order of binding follows the order: [C 8 mim] + < [C 6 mim] + < [C 4 mim] + < [C 2 mim] + for both [Cl] − and [Tf 2 N] − ; the same order excluding the [C 6 mim] + cation, which was not included in that work, was also found for [BF 4 ] − . Using Cooks’ kinetic method, Vitorino et al also confirmed the relative order of binding of the [C n mim] + cations to [Tf 2 N] − as [C 6 mim] + < [C 4 mim] + < [C 2 mim] + consistent with that observed by Bini et al These works suggest that the overall relative order of binding of the [C n mim] + cations to [BF 4 ] − follows the order: [C 8 mim] + < [C 6 mim] + < [C 4 mim] + < [C 2 mim] + . However, because the competitive experiments did not comprehensively examine other mixed clusters, and the energy-resolved experiments did not incorporate internal energy and unimolecular dissociation rates into the comparisons of the experimental data, there is still some uncertainty in this conclusion.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Based on the relative center-of-mass collision energies at 50% dissociation, the relative order of binding follows the order: [C 8 mim] + < [C 6 mim] + < [C 4 mim] + < [C 2 mim] + for both [Cl] − and [Tf 2 N] − ; the same order excluding the [C 6 mim] + cation, which was not included in that work, was also found for [BF 4 ] − . Using Cooks’ kinetic method, Vitorino et al also confirmed the relative order of binding of the [C n mim] + cations to [Tf 2 N] − as [C 6 mim] + < [C 4 mim] + < [C 2 mim] + consistent with that observed by Bini et al These works suggest that the overall relative order of binding of the [C n mim] + cations to [BF 4 ] − follows the order: [C 8 mim] + < [C 6 mim] + < [C 4 mim] + < [C 2 mim] + . However, because the competitive experiments did not comprehensively examine other mixed clusters, and the energy-resolved experiments did not incorporate internal energy and unimolecular dissociation rates into the comparisons of the experimental data, there is still some uncertainty in this conclusion.…”
Section: Introductionsupporting
confidence: 66%
“…The importance of elucidating absolute and relative trends in the structure, energetics, and reactivity of chemical systems has long been appreciated and has led to the development of absolute and relative cation and anion affinity scales for a wide variety of neutral and ionic systems. In particular, ESI tandem MS (ESI-MS/MS) approaches typically using collisional activation have been employed to examine the dissociation of IL clusters to establish cation–anion interaction scales for ILs. Several studies have examined the variable-energy CID behavior of cationic and anionic clusters of various ILs as a function of collision energy. In contrast to the threshold CID approach employed in our work, where energetic information is extracted at the onset of dissociation, these studies were based on comparisons at 50% dissociation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry and ion mobility spectrometry (IMS) have been powerful tools for elucidating the structure and examining the reactivity and reaction dynamics of IL clusters . Energy-resolved collision-induced dissociation (CID) experiments have been performed to elucidate the gas-phase energetics and dissociation mechanisms of aprotic and protic ILs for applications in space propulsion and to elucidate relative affinities of various cations and anions that comprise common ILs. IMS experiments have investigated the formation of IL clusters, IL cluster distributions and magic number clusters, and ion evaporation processes that occur during the ESI process. For example, IL clusters of the [5C:4A] + stoichiometry exhibit high stability, that is, magic number clusters, for at least two ILs. , Further, in addition to single ion-pair losses (C:A) upon dissociation, simultaneous loss of clusters involving multiple ion pairs, (C:A) n , has been reported for select IL clusters. , …”
Section: Introductionmentioning
confidence: 99%
“…In a study of anion/cation interaction by the kinetic method, 43 involving essentially organic cations and various anions, it is noticeable that the overlap between individual relative basicities to build a scale is not always fulfilled with the same precision as obtained in our measurements. In the case of the anion affinity scale reported by Vitorino et al, 43 this problem is likely due to the very different structures of the anions involved, which include fluorine, oxygen, carbon, and nitrogen bases with different degrees of electron delocalization. The possible limitations of the kinetic method in this regard deserve further investigations, if reliable experimental quantitative affinity scales are sought.…”
Section: ■ Experimental Sectionmentioning
confidence: 55%